Two-dimensional T-C 3 N functionalized with sodium: A promising platform for solid-state hydrogen storage - Laranjeira, José A.S. [UNESP]; Martins, Nicolas F. [UNESP]; Aparicio-Huacarpuma, Bill D.; Lima, Kleuton A.L.; Ribeiro, Luiz A.; Sambrano, Julio R. [UNESP] (Elsevier, 2025)
We report a comprehensive first-principles investigation of the two-dimensional carbon nitride monolayer T-C3N, focusing on its potential as a hydrogen storage material through sodium decoration. The pristine T-C3N structure exhibits a porous framework with an indirect band gap of 1.61 eV. Upon Na decoration, charge redistribution and metallic character are observed, which promote the adsorption of H2 molecules via van der Waals interactions. Na@T-C 3 N achieves a maximum storage capacity of 10.63 wt% with 16 adsorbed H2 molecules and average binding energies between –0.18 and –0.11 eV. Ab initio molecular dynamics simulations confirm the thermal stability of the system, with Na atoms remaining anchored and partial desorption of H2 at 300 K, indicating favorable reversibility.